Unsaturated hydraulic conductivity of a Yellow Podzolic soil in the north forest zone of Pernambuco State - Netto, André Maciel; Antonino, Antonio Celso Dantas; Audry, Pierre; Carneiro, Clemente José Gusmão; Olio, Attílio Dall (Pesquisa Agropecuaria Brasileira, 2000)
The determination of the hydraulic conductivity of a Yellow Podzolic soil was carried out during an experiment in a plot measuring 3.5 m x 3.5 m, at the Estação Experimental de Itapirema, Goiana, in the State of Pernambuco, Brazil. The internal drainage method was used to obtain the hydraulic conductivity (K(q)) as a function of soil water content, in the three main horizons of the soil. In relation to the methodological aspects, processing of data from internal drainage experiments, including the initial phase of fast drainage, the adjustment of the required parameters, it is necessary to use functions that reproduce the distinct transition between the fast and slow phases of drainage. From all five tested functions, those of power, sum of two exponentials and sum of three exponentials, especially this last one, adjusted well to this distinct transition. Three main horizons of the Yellow Podzolic soil were investigated for hydraulic conductivity. The sandy A horizon, with large pores, has a high conductivity while the BA horizon, with massive structure and few visible pores, has a low infiltration rate. The hydraulic dynamics of the Bt horizon is more complex due to its heterogeneity. The precise characterization of the A and BA horizons, which are the most important to agriculture and soil conservation, makes it possible to elaborate numeric simulation models of the water transference process in the surface horizons of this type of soil.